"As Usual, I'll Have to Take an IOU": W. E. B. Du Bois, the Gift of Black Music and the Cultural Politics of Obligation. (1st June 2017) - HEFFERNAN, NICK
Abstract : In The Souls of Black Folk (1903) W. E. B. Du Bois described African American music as a "gift" to America, contesting the tendency to regard white interest in black culture as appropriation or theft. Yet this metaphor invoked the complex circuits of indebtedness and obligation that are intrinsic to gift exchange in anthropological accounts of the practice, challenging white recipients of the gift to make adequate response. This challenge is most systematically addressed in a sequence of films that tell stories about white enthusiasm for the blues. The Blues Brothers (1980), Crossroads (1986), Blues Brothers 2000 (1998) and Black Snake Moan (2006) depict the blues as a gift and explore how whites might appropriately acknowledge and reciprocate for receiving it in a culture distorted by racial inequalities. The films develop a distinct set of narrative conventions for handling the politics of racial obligation, vacillating between seeing black music as a transracial cultural resource on the one hand and as a racially defined, inalienable possession of African Americans on the other. Using these same conventions, Honeydripper (2007) invites us to see the process of cultural exchange from a different perspective in which the problematic status of the blues as racialized property is diminished.